CASSANDRA - A simulation-based, decision-support tool for energy market stakeholders - Vavliakis, Konstantinos; Chrysopoulos, Anthony; Chatzidimitriou, Kyriakos; Symeonidis, Andreas; Mitkas, Pericles (EAI Endorsed Transactions on Energy Web, 2015)
Energy gives personal comfort to people, and is essential for the generation of commercial and societal wealth. Nevertheless, energy production and consumption place considerable pressures on the environment, such as the emission of green- house gases and air pollutants. They contribute to climate change, damage natural ecosystems and the man-made environment, and cause adverse effects to human health. Lately, novel market schemes emerge, such as the formation and operation of customer coalitions aiming to improve their market power through the pursuit of common benefits. In this paper we present CASSANDRA, an open source 1 , expandable software platform for modelling the demand side of power systems, focusing on small scale consumers. The structural elements of the platform are a) the electrical installations (i.e. households, commercial stores, small industries etc.), b) the respective appliances installed, and c) the electrical consumption-related activities of the people residing in the installations. CASSANDRA serves as a tool for simulation of real demand- side environments providing decision support for energy market stakeholders. The ultimate goal of the CASSANDRA simulation functionality is the identification of good practices that lead to energy efficiency, clustering electric energy consumers according to their consumption patterns, and the studying consumer change behaviour when presented with various demand response programs.